Ask Questions, Get Answers

Want to ask us a question? Click here
Browse Questions
Home  >>  CBSE XI  >>  Math  >>  Binomial Theorem
0 votes

Show that the middle term in the expansion of $(x-\large\frac{1}{x})^{2n}$ is $\large\frac{1\times 3\times 5\times..... (2n-1)}{n!}$$\times (-2)^n$

Can you answer this question?

1 Answer

0 votes
  • $T_{r+1}=nC_rx^{n-r}b^r$
Clearly the number of terms in the expansion of $(x-\large\frac{1}{x})^{2n}$ is $2n+1$
So,middle term =$(n+1) ^{th}$ term=$t_{n+1}$
$\Rightarrow t_{n+1}=(-1)^n 2nC_n.x^{2n-n} .(\large\frac{1}{x})^n$
$\Rightarrow (-1)^n 2nC_n.x^n .\large\frac{1}{x^n}$
$\Rightarrow (-1)^{n}\large\frac{(2n)!}{(n!)\times (n!)}$
$\Rightarrow (-1) ^n \large\frac{}{(n!)\times (n!)}$
$\Rightarrow (-1) ^n \large\frac{[1.3.5......(2n-3)(2n-1)][2.4.6.....(2n-2)2(n)]}{(n!)(n!)}$
$\Rightarrow (-1)^n [1.3.5.....(2n-1)\times 2^n \times [1.2.3(n-1).n]$
$\Rightarrow (-1)^n \large\frac{1.3.5.....(2n-1)}{n!}$$\times 2n$
$\Rightarrow \large\frac{1.3.5.....(2n-1)}{n!}$$\times [-2]^n$
Hence proved.
answered Jun 24, 2014 by sreemathi.v

Related questions

Ask Question
student study plans
JEE MAIN, CBSE, AIPMT Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App